Analisis Yuridis Terhadap Pemberlakuan European Union Deforestation Regulation (EUDR) Terhadap Perdagangan Indonesia (Menurut Aliran Sociological Yurisprudence) - Hardiawan, Ridwan; Sutrisno, Andri (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2025)
The European Union (EU) issued a regulation on deforestation, known as the European Union Deforestation-Free Regulation (EUDR), which has caused upheaval in the global commodity industry. Starting December 31, 2020, the EUDR regulation enforces due diligence on companies placing goods linked to deforestation and forest degradation on the EU market. These goods include beef, chocolate, coffee, palm oil, rubber, soy, and timber. Under the EUDR, these seven commodities and their related products must meet requirements related to deforestation and forest degradation to be sold or exported to the EU market.According to Roscoe Pound, a legal expert from the Sociological Jurisprudence school of thought, law should be viewed as a social institution that functions to meet societal needs. He argued that the task of legal science is to develop a framework that maximizes the fulfillment of social needs so that the law can serve as a means of social change. Therefore, a legal study on the application of the EUDR to Indonesia's trade with the EU should assess whether it aligns with the principles of law formation according to Roscoe Pound's Sociological Jurisprudence perspective.